2017
DOI: 10.24272/j.issn.2095-8137.2017.032
|View full text |Cite
|
Sign up to set email alerts
|

创制动物模型,为何不用树鼩呢?

Abstract: The Chinese tree shrew (Tupaia belangeri chinensis), a squirrel-like and rat-sized mammal, has a wide distribution in Southeast Asia, South and Southwest China and has many unique characteristics that make it suitable for use as an experimental animal. There have been many studies using the tree shrew (Tupaia belangeri) aimed at increasing our understanding of fundamental biological mechanisms and for the modeling of human diseases and therapeutic responses. The recent release of a publicly available annotated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…There are six subspecies of Tupaia belangeri in China, namely, T. belangeri gaoligongensis, T. belangeri modesta, T. belangeri yaoshanensis, T. belangeri tonquinia, T. belangeri yunalis and T. belangeri chinensis [9]. Previous studies have indicated that tree shrews are closely related to humans in genomic signature, biochemical metabolism and physiological function [10][11]. Due to its small body size, life span, short reproductive cycle and low cost of maintenance, tree shrews have been increasingly used as alternative laboratory animals in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…There are six subspecies of Tupaia belangeri in China, namely, T. belangeri gaoligongensis, T. belangeri modesta, T. belangeri yaoshanensis, T. belangeri tonquinia, T. belangeri yunalis and T. belangeri chinensis [9]. Previous studies have indicated that tree shrews are closely related to humans in genomic signature, biochemical metabolism and physiological function [10][11]. Due to its small body size, life span, short reproductive cycle and low cost of maintenance, tree shrews have been increasingly used as alternative laboratory animals in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this limitation, a non-human cell model supporting lytic replication of this virus is critical for the mechanism study of its strict species specificity. Previous reports implied that an animal with high similarity to human has a potential to be infected by HCMV [8], and the Chinese tree shrew was proved to be genetically close to primates and useful for pathological research of several human viruses [12]. Herein, we investigated the susceptibility of primary TSDF to HCMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the Chinese tree shrew (Tupaia belangeri chinensis) was found to be genetically close to primates and its genes or pathways playing a role in infectious diseases have higher identity to human [11,12]. Meanwhile, it has economical maintenance costs and a small body size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the unique genetic characteristics of tree shrews provide an opportunity for us to understand specific pathways mediated by the unique genes. For instance, loss of the important antiviral gene DDX58/RIG-I (retinoic acid inducible gene I) in the Chinese tree shrew has made the tree shrew a suitable animal model for studying viral infections (Fan et al, 2013;Xu et al, 2016;Yao, 2017).…”
Section: Introductionmentioning
confidence: 99%